The acute effects of high intensity resistance training on Resting energy expenditure and respiratory exchange ratio In overweight and obese women - Bakar, Nurul Shuhada Abu (Universiti Sains Malaysia, 2017)
The aim of the study is to investigate the acute effects of high intensity resistance training (HIRT) on resting energy expenditure (REE) and respiratory ratio (RER) in overweight and obese, non-trained women. Eight participants with mean age of 36.9±3.9 years volunteered for this research. They were divided into two groups which is HIRT group (n=4) and Control group (n=4). The HIRT group performed three exercises - inclined bench press, leg press and lat pull. The exercise consist of 3 sets with 6 reps followed by 20 sec rest, 2 or 3 reps followed by 20 sec rest and another 2 or 3 reps and rest for 2 min and 30 sec before the next exercise. The Control group maintained their usual routine. Using indirect calorimetry, metabolic gases were assessed in both HIRT and Control groups in using Cortex MetaMax3B portable metabolic system (MM3B, Leipzig, Germany). The measurements provided RER and variables required to calculate REE (kcal/day). Another metabolic gas assessment was conducted in the HIRT group 24 hours postexercise. For comparison of REE at baselines between groups, there were no significant differences detected. However, HIRT group showed increased REE, from 1890.7±520.7 significant changes in RER (p=0.22) 24 hours post-exercise in HIRT group. In conclusion, our study suggests that the short HIRT session may increase REE 24 hours change